Klasifikasi Tingkat Gangguan Tidur Menggunakan Algoritma Naïve Bayes - Iwan Ady Prabowo; Dwi Remawati; Aji Pratama Wisnu Wardana (STMIK Sinar Nusantara, 2020)
The Sleep disorder sometimes happens to someone unconsciously. Many health worker need a lot of time to detect the cause of sleep disorder, it is because there are some similar type of sleep disorder. The public health center in Karangmalang Sragen is needed a system to help the health workers to analyze the cause of sleep disorders. The aim of this research is to make a system to analyze the cause of sleep disorder by using the Naïve Bayes method. This research is conducted on Integrated Healthcare Center especially for the elderly in kedungwaduk. This research chooses the Naïve Bayes method to analyzing the type of sleep disorder experiences happen by the patient. The types of sleep disorders that used in this study were insomnia, hypersomnia, narcolepsy, sleep terror, disturbed sleep schedules and nightmares. The result in this study is patients can get solution about their sleep disorder, and also it can reduce the bad effect for the patient. The validation result of the Naïve Bayes method showed that 80% data was accuracy and it will be compared between 10 data from diagnostic test and 30 testing data.Keywords : Sleep disturbance, diagnosis, naïve bayes